The Effect of Encapsulated Apigenin Nanoparticles on HePG-2 Cells through Regulation of P53 - Mayada Mohamed Mabrouk Zayed; Heba A. Sahyon; Nemany A. N. Hanafy; Maged A. El-Kemary (MDPI AG, 2022)
Apigenin (Ap) is one of the most important natural flavonoids that has potent anticancer activity. This study was designed, for the first time, to load Ap into chitosan to improve its hydrophobicity and then it was coated with albumin-folic acid to increase its stability and bioavailability and to target cancer cells. The newly developed encapsulated Ap (Ap-CH-BSA-FANPs) was characterized and tested in vitro. The zeta potential of −17.0 mV was within the recommended range (−30 mV to +30 mV), indicating that encapsulated apigenin would not quickly settle and would be suspended. The in vitro results proved the great anticancer activity of the encapsulated apigenin on HePG-2 cells compared to pure Ap. The treated HePG-2 cells with Ap-CH-BSA-FANPs demonstrated the induction of apoptosis by increasing p53 gene expression, arresting the cell cycle, increasing caspase-9 levels, and decreasing both the MMP9 gene and Bcl-2 protein expression levels. Moreover, the higher antioxidant activity of the encapsulated apigenin treatment was evident through increasing SOD levels and decreasing the CAT concentration. In conclusion, the Ap-CH-BSA-FANPs were easy to produce with low coast, continued drug release, good loading capacity, high solubility in physiological pH, and were more stable than the formerly Ap-loaded liposomes or PLGA. Moreover, Ap-CH-BSA-FANPs may be a promising chemotherapeutic agent in the treatment of HCC.